2009
DOI: 10.1159/000242355
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Costimulatory Molecules in Allergic Disease and Asthma

Abstract: The prevalence of allergic diseases has increased rapidly in recent years. It is well established that the deleterious allergic response is initiated by T-cell recognition of major histocompatibility class II-peptide complexes at the surface of antigen-presenting cells. While this first signal gives antigen specificity to the adaptive immune response, a second nonspecific costimulatory signal is required by T cells to become fully activated. This signal is provided by interactions between antigen-presenting ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 177 publications
(110 reference statements)
3
45
0
1
Order By: Relevance
“…the promotion of Th2-cell activation (26)(27)(28). The first signal is the formation of antigen-MHC complexes on the mDC surface that bind specifically with the T-cell receptor-CD3 receptor complex on T-cell surfaces, and the second signal is co-stimulatory molecule expression and functional activation on the mDC surfaces that specifically bind to receptors on naïve T cells; the two signals form a co-stimulatory pathway (29). It has also been suggested that there is a third signal (30), as certain cellular molecules produced by DCs, such as thymic stromal lymphopoietin (TSLP), affect the direction of Th-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…the promotion of Th2-cell activation (26)(27)(28). The first signal is the formation of antigen-MHC complexes on the mDC surface that bind specifically with the T-cell receptor-CD3 receptor complex on T-cell surfaces, and the second signal is co-stimulatory molecule expression and functional activation on the mDC surfaces that specifically bind to receptors on naïve T cells; the two signals form a co-stimulatory pathway (29). It has also been suggested that there is a third signal (30), as certain cellular molecules produced by DCs, such as thymic stromal lymphopoietin (TSLP), affect the direction of Th-cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The noncanonical pathway is involved in development of the immune system and in adaptive immune responses, but its role in asthma and COPD has not been explored in detail. The coactivator molecule CD40 is expressed on antigen-presenting cells, such as dendritic cells and macrophages, activates the noncanonical pathway when it interacts with CD40L expressed on lymphocytes, and may amplify allergic responses in asthma (Lombardi et al, 2010). CD40 Fig.…”
Section: Nuclear Factor-kb Inhibitionmentioning
confidence: 99%
“…In addition to cDCs, CCR2 + monocytederived DCs are recruited to the conducting airways by CCL2 or CCL7 chemokines produced by lung epithelial cells (ECs) in response to allergen stimulation (4), After allergen uptake, DCs of both origins undergo a switch from the Ag-sampling into an Agpresenting mode associated with the upregulation of adhesion, MHC-II, and costimulatory molecules, including CD40, CD80, and CD86 (5), and migrate to the mediastinal lymph nodes (mLN) (5,6). The three signals provided by MHC-II/TCR, costimulatory molecule interaction, and cytokines produced by allergen-loaded DCs then pave the way for maladaptive Th2/Th17 skewing of naive CD4 + T cells (7,8). Several studies, in which complement factors or receptors have been deleted, point toward an important role for the complement system as a critical regulator of asthma development through its functions on DCs (9).…”
Section: /2mentioning
confidence: 99%